Cerebral autoregulation in children with traumatic brain injury: Comparing the autoregulatory index (ARI) to pressure reactivity index (PRx) and their associations with cerebral physiological parameters - Patel, Maryam (Division of Neurosurgery, 2018)
As an important hemodynamic mechanism, pressure autoregulation protects the brain against inappropriate fluctuations in cerebral blood flow subject to changing cerebral perfusion pressures. In acute neurological illnesses, including traumatic brain injury in children, impaired autoregulation is associated with a worse prognosis. It also has important clinical implications for managing blood pressure and intracranial pressure. Two common methods of measuring pressure autoregulation reported in the adult literature have been rarely reported in children. This pilot study aimed to examine the relationship between two autoregulatory indices, namely PRx (pressure reactivity index) and ARI (autoregulatory index) in children with severe TBI. The study also examined their relationship with the response of clinically relevant variables such as intracranial pressure (ICP), brain oxygenation (PbtO2) and local cerebral blood flow (loCBF) to dynamic testing. The study is a retrospective cohort study of prospectively collected data conducted at the Red Cross Children Hospital. We analyzed the results of 18 patients in 28 tests of autoregulation to determine the static state of autoregulation by calculating the autoregulatory index (ARI). These tests were done by controlled elevation of blood pressure to evaluate changes in transcranial Doppler-derived flow velocity of the middle cerebral artery. Concomitant recordings were made of ICP, PbtO2, and loCBF. Secondly, we also calculated the PRx as a moving correlation co-efficient between slow changes in blood pressure and ICP. Two time epochs of PRx were examined in relation to the static tests: 1 hour before and after the test, and 12 hours before and after the test. The results included 28 tests done for ARI and 27 calculations for PRx epochs; all tests had ICP and PbtO2 data and 23 had loCBF. PRx and ARI showed no significant relationship between them. However, there was a significant relationship between ARI and ΔICP (p=0.04), i.e. when autoregulation was weak the change in ICP with a change in blood pressure was greater; and between PRx and ΔPbtO2 (p=0.04). There was a trend in correlation analysis between loCBF and PRx but not in the linear mixed effects model In conclusion, the study showed no correlation between the two autoregulatory indices, PRx and ARI, probably because they assess different aspects of autoregulation. However, significant relationships exist between ARI and ΔICP as well as PRx and ΔPbtO2, which generate interesting hypotheses about autoregulation and have clinical implications. Both autoregulatory indices have benefits and limitations. Further studies on such relationships, taking into consideration a larger sample group, inclusion of unstable patients, and utilization of the same range in BP for calculating the indices, are recommended.